Analysis of User Journey Mapping Factors to Enhance User Experience in the Tokopedia Mobile E-Commerce Application - Darma Paramartha, I Gusti Ngurah; Sofyan, Yohanes Samuel; Permana, Gusi Putu Lestara (Information Technology and Science (ITScience), 2024)
Recent technological advancements have significantly transformed human life, particularly with the advent of the Fourth Industrial Revolution, which has profoundly influenced the use of the internet for business and economic activities. E-commerce has emerged as a crucial medium for online buying and selling, propelled by these digital advancements. This growth is especially evident in Indonesia, which ranks among the countries with the highest number of internet users globally. This study aims to identify the dominant factors influencing user journey mapping and their impact on the user experience of Tokopedia mobile application users. The research sample comprises 125 users of the Tokopedia application, with data collected through questionnaires distributed via Google Forms. The analysis involves factor analysis and simple linear regression. The findings reveal that the dominant factors influencing user journey mapping are user persona and opportunity. Furthermore, the study demonstrates that user journey mapping positively impacts the user experience for Tokopedia application users. This research underscores the importance of understanding user journey mapping in enhancing the overall user experience, which is crucial for e-commerce platforms like Tokopedia. The insights gained from this study can assist developers and marketers in better tailoring their strategies to improve user engagement and satisfaction. This study provides valuable perspectives on how user journey mapping can be utilized as a strategic tool to optimize user interactions and ensure that each step in the user journey delivers maximum value. Thus, user journey mapping not only enhances individual experiences but also contributes to the overall success of e-commerce platforms in an increasingly competitive market.